Agee - Agee, James, 1909-1955.; James Agee Film Project (New York : Reeves Teletape, 1985)
Reviews James Agee's life and works, including his childhood in Tennessee, his career as a journalist, his marriages, his career as a film critic and screenwriter, and dramatized excerpts from several of his novels.
VHS format.
Keywords: Agee, James, -- 1909-1955.; Authors, American -- 20th century -- Biography